Proceedings of the 2021 Conference of the North American Chapter of the Association for Computational Linguistics: Human Langua 2021
DOI: 10.18653/v1/2021.naacl-demos.2
|View full text |Cite
|
Sign up to set email alerts
|

Machine-Assisted Script Curation

Abstract: We describe Machine-Aided Script Curator (MASC), a system for human-machine collaborative script authoring. Scripts produced with MASC include (1) English descriptions of sub-events that comprise a larger, complex event;(2) event types for each of those events;(3) a record of entities expected to participate in multiple sub-events; and (4) temporal sequencing between the sub-events. MASC automates portions of the script creation process with suggestions for event types, links to Wikidata, and sub-events that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In those cases, we showed that human curation can step in timely and improve the quality of event schema when LLM-based models make mistakes 7 . In addition, our interface is easy to use, with much shorter time required to complete each event schema task compared to previous work (Ciosici et al, 2021).…”
Section: User Evaluationmentioning
confidence: 98%
See 4 more Smart Citations
“…In those cases, we showed that human curation can step in timely and improve the quality of event schema when LLM-based models make mistakes 7 . In addition, our interface is easy to use, with much shorter time required to complete each event schema task compared to previous work (Ciosici et al, 2021).…”
Section: User Evaluationmentioning
confidence: 98%
“…Another area related to our work is human-in-theloop schema generation, where annotators collaborate with computational models to create highquality event schema. In this field, one of the closest approachs is the Machine-Assisted Script Curation (Ciosici et al, 2021) created for script induction. With a fully interactive interface, they have shown the feasibility of realtime interaction between humans and pre-trained LLMs (e.g.…”
Section: Human-in-the-loop Schema Curation Interfacementioning
confidence: 99%
See 3 more Smart Citations